2013
DOI: 10.1007/s10059-013-0152-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential Anoxic Expression of Sugar-Regulated Genes Reveals Diverse Interactions between Sugar and Anaerobic Signaling Systems in Rice

Abstract: The interaction between the dual roles of sugar as a metabolic fuel and a regulatory molecule was unveiled by examining the changes in sugar signaling upon oxygen deprivation, which causes the drastic alteration in the cellular energy status. In our study, the expression of anaerobically induced genes is commonly responsive to sugar, either under the control of hexokinase or non-hexokinase mediated signaling cascades. Only sugar regulation via the hexokinase pathway was susceptible for O 2 deficiency or energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…In a transient expression experiment that used the RAmy3D : LUC reporter and effectors ( OsHXK7 and its catalytically inactive mutants OsHXK7‐G76D and OsHXK7‐S148A ), we clearly found that the Glc repression of RAmy3D is mediated by OsHXK7 under aerobic conditions (Figure ) and abolished under O 2 ‐deficient conditions (Figure ). This is consistent with our previous finding that the Glc repression of RAmy3D is susceptible under O 2 ‐deficient conditions (Lim et al ), suggesting that sugar signaling and cellular energy status most likely communicate with each other and influence the anaerobic induction of gene expression in rice. This interesting feature of deregulating the Glc repression of RAmy3D is that it enables the maintenance of high levels of sugar, which can sufficiently fuel the fermentation process under O 2 ‐deficient conditions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In a transient expression experiment that used the RAmy3D : LUC reporter and effectors ( OsHXK7 and its catalytically inactive mutants OsHXK7‐G76D and OsHXK7‐S148A ), we clearly found that the Glc repression of RAmy3D is mediated by OsHXK7 under aerobic conditions (Figure ) and abolished under O 2 ‐deficient conditions (Figure ). This is consistent with our previous finding that the Glc repression of RAmy3D is susceptible under O 2 ‐deficient conditions (Lim et al ), suggesting that sugar signaling and cellular energy status most likely communicate with each other and influence the anaerobic induction of gene expression in rice. This interesting feature of deregulating the Glc repression of RAmy3D is that it enables the maintenance of high levels of sugar, which can sufficiently fuel the fermentation process under O 2 ‐deficient conditions.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, the rice aamylase isoform, RAmy3D, is highly upregulated in O 2deficient rice seedlings. While a number of anaerobically induced genes demonstrate sugar-repressible transcription under aerobic conditions, we recently found an interesting and distinct feature that a subset of these genes including RAmy3D abolishes sugar repression under O 2 -and energydeficit conditions (Lim et al 2013). This suggests that a branch of the sugar-signaling cascades may be specifically affected by perturbed cellular energy status, which is possibly sensed by the energy-sensing system of SNF1-related protein kinase (SnRK1) (Baena-Gonzalez et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Relative to the expression levels of control samples, the decrease in HXK6 expression in submerged coleoptiles in japonica varieties (Nipponbare, 8391, and 352) was greater than that in indica varieties (IR64, 8341, and 8322). Hexokinases have been suggested to function as glucose sensors (Cho et al 2006 ; Cho et al 2009 ; Granot et al 2014 ; Granot et al 2013 ) that modulate the mechanisms associated with hypoxia and sugar starvation (Lim et al 2013 ; Yim et al 2012 ). Based on the evidence, HXK6 may be a major factor affecting the phenotypic variations observed in the Nipponbare/IR64-derived RIL population.…”
Section: Resultsmentioning
confidence: 99%
“…Os07g0674800, which encodes an ethylene-response factor and is induced by salinity, 36 drought, 37 cold, 38 and anoxia 39 and in transgenic rice plants overexpressing the stress-responsive gene OsNAC5, which encodes a NAC domain-protein, 40 was up-regulated by ethylene, abscisic acid, and jasmonic acid treatments. Os11g0210500 and Os11g0443700, which encode alcohol dehydrogenases and are induced by anoxia, 41,42 were up-regulated by ethylene and jasmonic acid. Os11g0701000 and Os11g0701400, which encode chitinases and are induced by jasmonic acid 43 and in the OsNAC5 overproducer, 40 were up-regulated by jasmonic acid.…”
Section: E1396404-4mentioning
confidence: 99%